2014
DOI: 10.1111/cei.12262
|View full text |Cite
|
Sign up to set email alerts
|

Immune deficiency in Ataxia-Telangiectasia: a longitudinal study of 44 patients

Abstract: SummaryAtaxia-Telangiectasia (A-T) is a genetic condition leading to neurological defects and immune deficiency. The nature of the immune deficiency is highly variable, and in some cases causes significant morbidity and mortality due to recurrent sinopulmonary infections. Although the neurological defects in A-T are progressive, the natural history of the immune deficiency in A-T has not been evaluated formally. In this study we analyse the clinical history and immunological data in 44 patients with A-T who at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 19 publications
(19 reference statements)
1
36
1
Order By: Relevance
“…Diseases of the respiratory system cause significant morbidity and are a frequent factor or cause of death in the A-T population [20,30-32]. Several factors contribute to the increased susceptibility to respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases of the respiratory system cause significant morbidity and are a frequent factor or cause of death in the A-T population [20,30-32]. Several factors contribute to the increased susceptibility to respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…If recurrent respiratory tract infections present later in life, then other contributory factors (e.g. cough/swallowing difficulties, neuromuscular abnormalities or underlying lung disease) are a more likely explanation [27].…”
Section: Does Immune Deficiency Progress?mentioning
confidence: 99%
“…A high proportion (74%) of children with A-T are prescribed prophylactic antibiotics [24] on inconsistent and non-evidence-based criteria. A longitudinal follow-up study (mean duration of follow-up 5 years) found that 30 (68%) out of 44 patients were commenced early on prophylactic antibiotics with an aim to reduce the frequency and severity of bacterial respiratory infections [27]. The proportion of patients with A-T who had chronic respiratory symptoms and were using chronic macrolide antibiotics was lower in the patients in the USA (12 out of 36 A-T patients alive and 0 out of 65 A-T patients who died secondary to lung disease); however comparative data for patients with A-T who did not have chronic respiratory symptoms were not available [17].…”
Section: Antibioticsmentioning
confidence: 99%
“…1 Until now, immune dysfunction in AT has been characterized by improper B-and T-cell maturation, [2][3][4][5] immunoglobulin deficiencies, and impaired antibody responses observed in about two-thirds of patients. 6,7 Patients often have recurring respiratory tract infections and chronic interstitial inflammatory lung disease, although opportunistic infections are uncommon. 8,9 Many symptoms in AT patients, including increased incidence of autoimmunity, 10 oxidative stress, 11 cardiovascular disease, insulin resistance, and elevated serum levels of inflammatory cytokines, 12,13 suggest that they also suffer from pathologic inflammation.…”
Section: Introductionmentioning
confidence: 99%